Understanding the digital transformation on the telecom companies and covid19 effect on the employment - Benayan, Mohammed; Obeidat, Marsail (International Journal of Engineering and Technology, 2024)
This article delves into the digital transformation on the telecom companies and COVID-19 effect on the employment explores the impact of digital transformation in the telecommunications sector, particularly in the context of the COVID-19 pandemic. It examines how digital advancements have reshaped corporate processes, culture, and customer experiences, leading to significant changes in the telecom industry. The research also delves into the effects of these transformations on employment within telecom companies, both before and after the COVID-19 outbreak. The document aims to understand the implications of automation and digitalization on jobs and to assess the role of COVID-19 in accelerating these changes.